Immunohistochemical characteristics of local sites that trigger atrial arrhythmias in response to high-frequency stimulation. Issue 2 (19th October 2022) - Kim, Min-young; Nesbitt, James; Koutsoftidis, Simos; Brook, Joseph; Pitcher, David S; Cantwell, Chris D; Handa, Balvinder; Jenkins, Catherine; Houston, Charles; Rothery, Stephen; Jothidasan, Anand; Perkins, Justin; et al.
Abstract: Aims: The response to high frequency stimulation (HFS) is used to locate putative sites of ganglionated plexuses (GPs), which are implicated in triggering atrial fibrillation (AF). To identify topological and immunohistochemical characteristics of presumed GP sites functionally identified by HFS. Methods and results: Sixty-three atrial sites were tested with HFS in four Langendorff-perfused porcine hearts. A 3.5 mm tip quadripolar ablation catheter was used to stimulate and deliver HFS to the left and right atrial epicardium, within the local atrial refractory period. Tissue samples from sites triggering atrial ectopy/AF (ET) sites and non-ET sites were stained with choline acetyltransferase (ChAT) and tyrosine hydroxylase (TH), for quantification of parasympathetic and sympathetic nerves, respectively. The average cross-sectional area (CSA) of nerves was also calculated. Histomorphometry of six ET sites (9.5%) identified by HFS evoking at least a single atrial ectopic was compared with non-ET sites. All ET sites contained ChAT-immunoreactive (ChAT-IR) and/or TH-immunoreactive nerves (TH-IR). Nerve density was greater in ET sites compared to non-ET sites (nerves/cm 2 : 162.3 ± 110.9 vs. 69.65 ± 72.48; P = 0.047). Overall, TH-IR nerves had a larger CSA than ChAT-IR nerves (µm 2 : 11 196 ± 35 141 vs. 2070 ± 5841; P < 0.0001), but in ET sites, TH-IR nerves were smaller than in non-ET sites (µm 2 : 6021 ± 14 586 vs. 25 254 ± 61 499; P < 0.001). Conclusions: ET sites identified by HFS contained a higher density of smaller nerves than non-ET sites. The majority of these nerves were within the atrial myocardium. This has important clinical implications for devising an effective therapeutic strategy for targeting autonomic triggers of AF.